Estéticas da prisão : diálogos entre literatura e cinema - Freitas, Norma de Siqueira (2008)
This study aims at analyzing both the autobiographic account entitled Memórias do Cárcere, by Graciliano Ramos, in comparison with the homonymous motion picture by Nelson Pereira dos Santos, and the book Estação Carandiru, by Drauzio Varella, in comparison with its filmic transposition called Carandiru, performed by Hector Babenco. The focus is the relation between body, imprisonment, and pain and their representability, taking into consideration the inherited particularities of each artistic modality, namely cinema and literature. The productions approached in this thesis present to the reader and to the spectator a panel of the 20th century Brazilian society in two different moments: a view of the first half in opposition to the three last decades. Due to their evident hybridism and their singularity in language, both narratives defy traditional concepts of genres in both vehicles under study and make themselves genuine depictions of contemporary fragmentation. Apart from their essential differences, such literary and filmic works, as they disclose the prison universe, expose an excluding and violent scenery that consolidates the image of the Brazilian nation.